2009
DOI: 10.1002/j.1681-4835.2009.tb00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Animal Health Knowledge Gaps in Southern Countries: The Creation of a 2D Animal Health Resource Room

Abstract: Livestock are a key asset for the global poor. However, access to relevant information is a critical issue for both livestock development practitioners and the poor themselves. Therefore, the following paper details the creation of an on-line Animal Health Resource Room. The aim was to create an immersive environment, which mimics the benefits of a 3D Virtual Learning Environment without the constraints on download times. Therefore, in the following paper key issues in the dissemination of such a platform such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Nevertheless, when asked if the vet should replace the Guru as the single character in the program, most participants felt this would make the information less accessible. Indeed, in India, veterinarians due to notions regarding social exclusion are often not utilised by the poor (Heffernan et al, 2009). Equally, problematic, respondents noted that vets had a very prescribed role in animal health as opposed to livestock production and husbandry.…”
Section: Figure 4 Guru Character Imentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, when asked if the vet should replace the Guru as the single character in the program, most participants felt this would make the information less accessible. Indeed, in India, veterinarians due to notions regarding social exclusion are often not utilised by the poor (Heffernan et al, 2009). Equally, problematic, respondents noted that vets had a very prescribed role in animal health as opposed to livestock production and husbandry.…”
Section: Figure 4 Guru Character Imentioning
confidence: 99%
“…A number of studies have shown that information regarding animal health in developing countries is extremely uneven (LDG, 2003;IFAD, 2004;Heffernan, 2005;Lin and Heffernan, 2009; 2010) and tools for information transfer are under-developed. While large strides have been made in the human health with regard to information technologies (see Kushniruk, 2011;Gonzalez et al, 2011;Lee and Berge, 2011), the animal health sector has been largely left behind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 3D applications are already diffusing from North to South (largely as part of gaming applications). Further, given the rapid advance of broadband in southern countries (see Lin and Heffernan 2009), the 3D platform offered a unique opportunity to identify issues related to both present and future user demand.…”
Section: Introductionmentioning
confidence: 99%